Altered neurovascular coupling as measured by optical imaging: a biomarker for Alzheimer's disease. Issue 1 (December 2017) - Kotliar, Konstantin; Hauser, Christine; Ortner, Marion; Muggenthaler, Claudia; Diehl-Schmid, Janine; Angermann, Susanne; Hapfelmeier, Alexander; Schmaderer, Christoph; Grimmer, Timo
Abstract Neurovascular coupling can be directly assessed by retinal vessel response to flickering light using optical imaging methods. The response is altered in a number of ocular and cardiovascular diseases. Whether it is altered in Alzheimer's disease (AD) is investigated. Retinal vessel reaction to monochromatic flicker stimulation was examined by Dynamic Vessel Analyzer independent of the commercial software in elderly subjects: 15 patients with mild-to-moderate dementia due to AD (ADD); 24 patients with mild cognitive impairment due to AD (MCI); 15 cognitively healthy controls (HC). Retinal vessels in ADD showed a more emphasized and delayed reactive dilation as compared to HC. In MCI, these aspects still differed from those seen in ADD. Maximal arterial reaction was increased and dilation was delayed in ADD as compared to HC (p = 0.004 and p < 0.001) and to MCI (p = 0.058 and p = 0.004), respectively. Maximal venous reaction was increased in ADD as compared to HC (p = 0.001) and to MCI (p = 0.007), respectively. This finding suggests that retinal neuronal activity is either increased or feed-back loop of neurovascular coupling is damaged with differentiating alterations across the spectrum of AD. Thus, retinal vessel reaction to flicker stimulation is considered a promising non-invasive, widely available and easy-to-administer future biomarker for the diagnosis and monitoring of AD.